Smart Cities and Social Disruption: A Study of Changes in The Patterns of Interaction Among Urban Residents in Palangka Raya - Sriyana Sriyana; Wiwik Suprapti; Muhlis Muhlis (International Journal of Social Sciences, Language, and Education, 2026)
The integration of digital infrastructure within the smart city framework of Palangka Raya has fundamentally reconstructed the communication paradigms and sociological structures of its urban residents. This empirical inquiry investigates the complex transition from conventional face-to-face engagements to technologically mediated networks, examining the accompanying social disruptions and emergent community resiliencies. Utilizing a qualitative case study design with a triadic data collection approach, this research identifies an expansion of spatial-social boundaries characterized by highly efficient yet increasingly impersonal relationships. The accelerated adoption of municipal platforms triggers systemic disruptions, manifested through widening digital divides, intensified individualization of daily routines, and a pronounced erosion of organic communal safety nets. Conversely, urban citizens demonstrate active agency by mobilizing self-taught digital literacy, establishing interest-driven cyber spaces, and re-engineering social schedules to balance virtual connectivity with physical cultural rituals. This dynamic synthesis culminates in the conceptualization of an adaptive hybrid society, demonstrating how developing urban populations maintain humanistic resilience and cultural identity while absorbing technocratic modernizations.